Information seeking at the intersection of search, learning, inquiry, and creativity: Sharing stories to inform creative research. Issue 1 (18th October 2019) - Twidale, Michael; Rieh, Soo Young
ABSTRACT: This alternative event brings together researchers, practitioners, and students who are interested in developing new research ideas and methods by engaging in a series of activities around sharing stories about information seeking that helped their learning and inspired their creativity. Although storytelling is well established within Library and Information Science, it is not normally used to inform research about search. However we believe it has great potential in inspiring creative research about creativity.